Anti-proliferative activity on drug-sensitive and drug-resistant erythroleukemic cells of Samor Pipek (Terminalia bellirica (Gaertn.) Roxb.) fruit extracts - Winit Choiprasert; Watcharaporn Khumsan; Pimchanok Malasaem; Bajaree Phithakham (Journal of Associated Medical Sciences, 2017)
Introduction: Cancer is a major cause of death in Thailand. Drug resistance in cancer is a significant obstacle to the success of chemotherapy in cancer. There are several researches indicate the potential of herb in the inhibition of cancer cell proliferation for applying in cancer treatment.